No digital divide? Technology use among homeless adults. Issue 1 (2nd January 2017) - Rhoades, Harmony; Wenzel, Suzanne L.; Rice, Eric; Winetrobe, Hailey; Henwood, Benjamin
ABSTRACT: Homeless adults experience increased risk of negative health outcomes, and technology-based interventions may provide an opportunity for improving health in this population. However, little is known about homeless adults' technology access and use. Utilizing data from a study of 421 homeless adults moving into PSH, this paper presents descriptive technology findings, and compares results to age-matched general population data. The vast majority (94%) currently owned a cell phone, although there was considerable past 3-month turnover in phones (56%) and phone numbers (55%). More than half currently owned a smartphone, and 86% of those used Android operating systems. Most (85%) used a cell phone daily, 76% used text messaging, and 51% accessed the Internet on their cell phone. One-third reported no past 3-month Internet use. These findings suggest that digital technology may be a feasible means of disseminating health and wellness programs to this at-risk population, though important caveats are discussed.